Developing the price competitiveness in project business : Case: International industrial company - Tenovuo, Karno (My University, 2018)
The purpose of the the research is to determine how can the price competitiveness of project businesses be further increased by developing the key drivers of the presale period. Thesis is important, because it brings new perspectives to the concept of price competitiveness and it can be used as reference in researching industrial price competitiveness, especially in project-based businesses. The research problem were divided in sub areas: what are the key drivers influencing price competitiveness in project-based business, which drivers can be developed before the actual sale and finally how key drivers should be developed in order to increase price competitiveness. Theoretical section of the thesis go through models and factors for price competitiveness. In the conclusion and discussion section a new model is introduced for analysing price competitiveness in project-based businesses. This model is an extension of the Kim & Maubourne's 2004 generic model. The new model is taking more factors into consideration regarding price competitiveness and gives examples how these can be developed. The new model goes deeper into project-based business and examines how different factors affect each other and opens the theories behind them as well. Theoretical part of the thesis can also be used as a guideline which factors to take into considerations when building new competitiveness businesses and how to rethink the whole process. The empirical part of the thesis was done by interviewing key people inside the case company. Based on the theoretical section, a large number of detailed questions and themes had been selected. The author itself had a long and deep background in the subjects and good understanding of the factors and models in real-life, because he had led project-based businesses and business development in project-based businesses his whole career. The research identifies which factors influence price competitiveness in general. These were studied which are specific ones for project-based businesses. Three factors are highlighted in project-based businesses: the role of supply chain, pricing model and the importance of development activities to secure the contract and correct price levels. In these three areas, the research offers a wide range of ways to develop the price competitiveness.
Keywords: price competitiveness, project business, pricing methods, business models, productivity development, stakeholder development, supply chain development, engineering development, international industrial company